Directive prohibition utterances with honorific politeness used by families in Makassarese community: An ethnolinguistic study - Nashruddin, Nashruddin; Syam, Ummi Khaerati; Waliyudin, Waliyudin; Fitrawahyudi, Fitrawahyudi (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2025)
Different ways are used in delivering prohibition utterances in a particular society. This research is important because it reveals social value, honor, and philosophical value reflected in prohibition utterances applied by families in Makassar society through an ethnolinguistic lens. Therefore, this research aims to find strategies to convey directive prohibition utterances with honorific politeness, philosophical reflected shown in prohibition utterances with honorific politeness strategies, and the pattern of directive prohibition utterances with honorific politeness strategies in the Makassar community families. An ethnolinguistic approach is used because the way Makassarese people speak is shaped by ethnic and customary values. This research applies qualitative research method. Data sources are utterances and field note results obtained from three families with Makassar ethnic background who live in Makassar city. To collect data, the researcher stayed in their homes. The results show that direct prohibition utterances are used more dominantly than indirect prohibition in family conversations in Makassar society. It indicates that the Makassar community tends to prioritize positive politeness, show closeness in relationships, and convey messages clearly and unambiguously. Those directive prohibition utterances contain philosophical values, namely honesty, firmness, clarity, spontaneity, affection, respect, and maintenance of harmonious relationships.